so...\(\displaystyle \frac{x+1}{x}-\frac{x}{x+1}=0 \)
\(\displaystyle \frac{(x+1)^2}{x(x+1)}-\frac{x^2}{x(x+1)}=0 \)
\(\displaystyle \frac{(x+1)^2-x^2}{x(x+1)}=0 \)
Can you continue the exercise?
No.
Since \(\displaystyle \frac{(x+1)^2-x^2}{x(x+1)}=0 \) , the numerator must be equal to zero, so \(\displaystyle (x+1)^2-x^2 =0 \).
CB1101, what Mathmari means is that the only way that a fraction can = 0 is if the numerator = 0. Does that make sense? I can have the most God awful fraction like this:
\(\displaystyle \dfrac{3x(x-1)(x-4)^3}{x^{e}(4x-3)^5(x^5-7x^3+8)^{\ln9}}=0\)
and all you have to do is set the numerator = 0 and solve. In this case x = 0, 1 and 4.
To be preciseI see what you're saying. So it becomes 0/(x(x+1)) = 0
I'm confused as to how to solve when there's a 0 in the numerator